РЕСПУБЛИКАМЫЗДЫҢ АЎЫЛ ХОЖАЛЫҒЫНДАҒЫ АЛЫП БАРЫЛЫП АТЫРҒАН ЖЕТИСКЕНЛИКЛЕР - Хожалепесов, П.З.; Зинатдинов, Б.П.; Жорабаева, Ж.К. (SCIENCE and SOCIETY, 2019)
The article is devoted to the description of the reforms in the agricultural sector of the republic. The author of the article also studies the ways of providing the agriculture of the republic with mineral fertilizers and ways of its financing in conditions of market economy.
Keywords: agrotechnical; mineral fertilizer; irrigation; macroeconomics; strategy; of action agriculture; appliances; technology; reform